Sosialisasi Penggunaan Qris Sebagai Solusi Modern Untuk Pembayaran Zakat Online Pada Masyarakat Desa Tapen - Rahmawati, Rina Dian; Aisa, Aufia; Khasanah, Fitrohtul; Sholihah, Diana Nur; Muslihah, Ana Milhatul; Damasanti, Alvina; Al-Husnin, Mohammad Iqbal Maulana; Agustin, Eni; Masruroh, A’ida; Rahman, Fathur (LPPM Universitas KH. A. Wahab Hasbullah, 2025)
Zakat plays a crucial role in fostering social welfare and reducing economic inequality. However, its implementation in rural areas, such as Desa Tapen, often faces challenges due to limited access to information and technology. In the digital era, zakat payments can be made more efficiently through QR CODE technology, specifically with the Quick Response Code Indonesian Standard (QRIS) system developed by Bank Indonesia. Nevertheless, online zakat payments have not yet been implemented in Desa Tapen due to the community's lack of knowledge about the platform. Therefore, there is a need for socialization regarding the use of QRIS as a modern solution for online zakat payments. It is hoped that this socialization will enhance the community’s understanding of the ease, security, and benefits of QRIS, encouraging the adoption of online zakat payments in Desa Tapen